Rare presentation of esophageal atresia with supra-esophageal atresia: a case report and management challenges - Suhandri, Wiwin; Hericos, Muhammad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Esophageal atresia (EA), often regarded as ’the epitome of modern surgery’, typically presents with tracheoesophageal fistula (TEF) and occurs in about 1 in 2400 to 1 in 3000 newborns, frequently accompanied by other congenital malformations. Rarely, EA is associated with congenital esophageal stenosis (CES), a condition first identified by Spitz. EA and TEF result from the incomplete development of the esophagus and trachea, with polyhydramnios in the third trimester being a potential indicator. This case study described a 43-year-old multiparous woman who, during an antenatal care examination, was found to have a fetus with abnormalities and excessive amniotic fluid, necessitating two amnioreduction procedures. Despite the interventions, the fetus exhibited signs of supra-esophageal atresia, leading to an elective cesarean section. The newborn, a girl with a birth weight of 3200 grams and an Apgar score of 5/6, could not be fitted with an orogastric tube, although karyotyping showed no chromosomal abnormalities. The discussion highlights the association of EA with various tracheobronchial anomalies and emphasizes the need for preserving the native esophagus in cases of CES. Gastroesophageal reflux disease (GERD) is common in EA patients, often requiring long-term follow-up and possible antireflux surgery. The case underscores the importance of diligent monitoring and intervention in high-risk pregnancies, with regular ANC examinations and accurate diagnoses being crucial for effective management.